Epidemic HI2 Plasmids Mobilising the Carbapenemase Gene blaIMP-4 in Australian Clinical Samples Identified in Multiple Sublineages of Escherichia coli ST216 Colonising Silver Gulls - Tarabai, Hassan; Wyrsch, Ethan R; Bitar, Ibrahim; Dolejska, Monika; Djordjevic, Steven P (Microorganisms, 2021)
Escherichia coli ST216, including those that carry blaKPC-2, blaFOX-5, blaCTX-M-15 and mcr-1, have been linked to wild and urban-adapted birds and the colonisation of hospital environments causing recalcitrant, carbapenem-resistant human infections. Here we sequenced 22 multiple-drug resistant ST216 isolates from Australian silver gull chicks sampled from Five Islands, of which 21 carried nine or more antibiotic resistance genes including blaIMP-4 (n = 21), blaTEM-1b (n = 21), aac(3)-IId (n = 20), mph(A) (n = 20), catB3 (n = 20), sul1 (n = 20), aph(3")-Ib (n = 18) and aph(6)-Id (n = 18) on FIB(K) (n = 20), HI2-ST1 (n = 11) and HI2-ST3 (n = 10) plasmids. We show that (i) all HI2 plasmids harbour blaIMP-4 in resistance regions containing In809 flanked by IS26 (HI2-ST1) or IS15DI (HI2-ST3) and diverse metal resistance genes; (ii) HI2-ST1 plasmids are highly related to plasmids reported in diverse Enterobacteriaceae sourced from humans, companion animals and wildlife; (iii) HI2 were a feature of the Australian gull isolates and were not observed in international ST216 isolates. Phylogenetic analyses identified close relationships between ST216 from Australian gull and clinical isolates from overseas. E. coli ST216 from Australian gulls harbour HI2 plasmids encoding resistance to clinically important antibiotics and metals. Our studies underscore the importance of adopting a one health approach to AMR and pathogen surveillance.
Keywords: wildlife; ST216; Australian silver gull; urban birds; anthropogenic pollution; Chroicocephalus novaehollandiae; whole genome sequencing